Fairy Tales and Inspirational Stories as A Medium for Character Development for Elementary School Children - Supriyono; Ardy Wiyani, Novan (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to examine the role of fables and inspirational stories as effective media in developing the character of elementary school children. An epistemological perspective is used as an analytical framework to understand how children construct knowledge and moral understanding through stories. This research employs a qualitative method with a case study approach. The research subjects are elementary school students in the lower grades. Data was collected through participant observation, in-depth interviews with teachers and students, and document analysis such as storybooks and learning activity notes. The research results show that fables and inspirational stories have great potential in shaping children's character. These stories not only provide entertainment but also teach important moral, social, and cultural values. Children learn about kindness, honesty, courage, cooperation, and empathy through the characters in the stories. In addition, stories also stimulate children's imagination, creativity, and critical thinking skills. From an epistemological perspective, children construct knowledge about morality through a process of social constructivism. They interact with stories, discuss with peers, and receive feedback from teachers. This process allows children to reflect on the actions of characters in the story and relate them to their own lives. This study suggests that fables and inspirational stories be integrated more systematically into the elementary school curriculum. Teachers can use stories as a starting point for class discussions, writing activities, or group projects. In addition, parents can also play an active role in reading stories to children at home and discussing the values contained therein.